36 Altered Prefrontal Cortex Responses in Older Adults with Subjective Memory Complaints and Dementia During Dual-Task Gait: An Fnirs Study. (20th December 2019) - Teo, Wei-Peng; Rantalainen, Timo; Macpherson, Helen
Abstract: In this study, we investigated the effects of walking during single-task and dual-task gait (STG and DTG) conditions, on left prefrontal cortex (L PFC) activation in older adults with subjective memory complaints (SMC) and Dementia. A total of 72 older adults (aged 65-94 yrs; 33 Healthy; 28 SMC; 11 Dementia) were recruited from the community and assisted living facilities. A portable 7m zeno walkway gait analysis mat was used to measure stride, velocity, length and duration during 4 passes of STG and DTG each. A portable single-channel functional near-infrared spectroscopy (fNIRS) device (Portalite, Artinis Medical Systems) was placed over the L PFC to measure changes in oxyhaemoglobin response (O2 Hb) during STG and DTG. One-way analysis of variance (ANOVA) with bonferroni post-hoc t -test for multiple comparisons was used to determine differences between groups. Our results showed that stride velocity, duration and length during STG (all p<0.05) and DTG (all p<0.000) were significantly impaired in the Dementia group compared to Healthy and SMC groups, while no significant differences were observed between Healthy and SMC groups. For STG, a greater increase in O2 Hb (p<0.05) was observed in the Dementia group compared to the Healthy and SMC groups, while no differences were observed between Healthy and SMC. However, a significant increase and decline in O2 Hb was observed during DTG in the SMC and Dementia groups respectively, compared to Healthy. Our findings indicate an altered pattern of cerebral haemodynamic response of the PFC in people with SMC and Dementia that may be indicative of cognitive demands of gait. Our findings may have implications for the use of DTG and fNIRS as a potential early biomarker for cognitive declines in older adults.